Biopolymer Composites with Ti/Au Nanostructures and Their Antibacterial Properties - Slepička, Petr; Fajstavr, Dominik; Krejčová, Markéta; Rimpelová, Silvie; Slepičková Kasálková, Nikola; Kolská, Zdeňka; Švorčík, Václav (Pharmaceutics, 2021)
In this study, we have aimed at the preparation and characterization of poly-l-lactic acid (PLLA) composites with antibacterial properties. Thin bilayers of titanium and gold of various thickness ratios were deposited on PLLA by a cathode sputtering method; selected samples were subsequently thermally treated. The surface morphology of the prepared composites was studied by atomic force, scanning electron, and laser confocal microscopy. The chemical properties of the composites were determined by X-ray photoelectron and energy-dispersive X-ray spectroscopy in combination with contact angle and zeta potential analyses. The antibacterial properties of selected samples were examined against a Gram-negative bacterial strain of E. coli. We have found that a certain combination of Au and Ti nanolayers in combination with heat treatment leads to the formation of a unique wrinkled pattern. Moreover, we have developed a simple technique by which a large-scale sample modification can be easily produced. The dimensions of wrinkles can be tailored by the sequence and thickness of the deposited metals. A selected combination of gold, titanium, and heat treatment led to the formation of a nanowrinkled pattern with excellent antibacterial properties.
Keywords: nanostructured surface; gold layer; antimicrobial activity; composites; antibacterial properties; titanium layer; biopolymer; thermal modification; surface morphology; wrinkled patterns